Antibody Response to SARS-CoV-2 Vaccination in Patients With Lymphoproliferative Disorders and Plasma Cell Dyscrasias: Anti-Lymphoma Therapy as a Predictive Biomarker of Response to Vaccination - Gung, Carol; McGuire, Regina; George, Mercy; Abdulkareem, Abdullateef; Belden, Katherine A.; Porcu, Pierluigi; Martinez-Outschoorn, Ubaldo; Binder, Adam F.; Chervenova, Inna; Alpdogan, Onder (Frontiers in Oncology, 2022)
We retrospectively analyzed SARS-CoV-2 vaccination antibody responses in a cohort of 273 patients with lymphoproliferative disorders or plasma cell dyscrasias who were seen at a single tertiary cancer center. Semi-quantitative anti-spike protein serologic testing was performed with enzyme immunoassay method. We found that the antibody response rate to SARS-CoV-2 vaccination was 74.7 % in our patient cohort with no difference based on gender, age or race. The highest response rate was found in patients with Multiple Myeloma (MM) (95.5%). The response rates found in Diffuse Large B-Cell Lymphoma (DLBCL), Chronic Lymphocytic Leukemia (CLL), and Low-Grade Non-Hodgkin Lymphoma (LG-NHL) were 73.2%, 61.5% and 53% respectively. We also evaluated the effects of receiving active chemo-immunotherapy on SARS-CoV-2 vaccination antibody response. We found that the patients on treatment had lower response than the patients off treatment (62.1% versus 84.4% p<0.001) Thirty-four of 56 LG-NHL patients were receiving anti-lymphoma treatment with a lower SARS-CoV-2 vaccination response as compared to the patients who were not on treatment (29.4% v 87.5% p<0.001). We observed a similar pattern in CLL patients receiving treatment (48.1 v 76.0 p:0.049). We found that only disease type and treatment status (on-treatment vs. off- treatment), but not gender, age or race were significant predictors of non-response in the multivariable logistic regression model. The interaction between disease type and treatment status was not statistically significant by multivariate analysis In conclusion, receiving anti-cancer treatment was found to play a significant role in decreasing the response to COVID-19 vaccination.